Americans View Their Mental Health, 1957 - Gurin, Gerald ([Verlag nicht ermittelbar], 1984)
In 1957, the United States Congress established the Joint Commission on Mental Illness and Health to evaluate the nation's resources for coping with both the psychological and economic problems of mental illness. The Commission sponsored a nationwide survey, which was conducted by the Survey Research Center at the University of Michigan, to assess the subjective mental health of "normal" American adults and to determine in detail how they coped with problems of adjustment. During the spring of 1957, a sample of American adults was interviewed on various areas in which problems might arise, including marriage, parenthood, employment, and general social relationships. Information about leisure time, past and present physical and mental health, and motives for affiliation, achievement, and power were also sought. Three questionnaire forms were employed, each addressed to a randomly selected third of the sample.